Condition monitoring of slow speed rotating machinery using stress waves - Mba, David Uzo (Cranfield University, 1998)
Condition monitoring through the use of vibration analysis is an established and effective technique for detecting loss of mechanical integrity of a wide range and classification of rotating machinery. Equipment rotating at low rotational speeds present an increased difficulty to the maintenance engineer, since conventional vibration measuring equipment is not capable of measuring the fundamental frequency of operation, also, component distress at low operational speeds does not necessarily show an obvious change in vibration signature. This thesis presents a study of high frequency stress wave analysis as a means of detecting early stages of loss of mechanical integrity in slow speed machinery, the first of its kind. Investigations were centred on the Rotating Biological Contactor (RBC) which is used for sewage treatment in small communities and rotates between 0 .6 to 1 revolutions per minute. The mechanism of stress wave generation was the relative movements between mating components that were experiencing loss of mechanical integrity, for instance, the loss of tightening torque between clamped components. Development of the stress wave monitoring technique was accomplished by firstly, simulating a variety of mechanical faults on the test-rig, and secondly, by numerous ‘on-site’ tests on operational RBCs and their bearings. In application of this technique to operational RBCs and bearings, as well as cataloguing evidence of mechanical deficiencies associated with RBCs operated within the Severn Trent Water region, the author inspected 261 RBCs and covered over 35,000 miles, contributing to the uniqueness of this research programme. This research has provided Severn Trent Water limited with a PC-based monitoring system comprising an AE transducer, pre/post amplifiers, ADC board and software on which all diagnosis was undertaken. Furthermore, during the process of investigating reasons for the mechanical failures of the RBC, technical information was uncovered thereby assisting Severn Trent Water in perusing a more robust design of RBC. Moreover this work has assisted Severn Trent Water to maintain that envious reputation that over a number of years not one of the RBC sewage treatment works has failed its consent level as set by the Environmental Agency.